If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 6x + 2 + 7 = 4x + 5 + 7x Reorder the terms: 2 + 7 + 6x + 6x = 4x + 5 + 7x Combine like terms: 2 + 7 = 9 9 + 6x + 6x = 4x + 5 + 7x Combine like terms: 6x + 6x = 12x 9 + 12x = 4x + 5 + 7x Reorder the terms: 9 + 12x = 5 + 4x + 7x Combine like terms: 4x + 7x = 11x 9 + 12x = 5 + 11x Solving 9 + 12x = 5 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 9 + 12x + -11x = 5 + 11x + -11x Combine like terms: 12x + -11x = 1x 9 + 1x = 5 + 11x + -11x Combine like terms: 11x + -11x = 0 9 + 1x = 5 + 0 9 + 1x = 5 Add '-9' to each side of the equation. 9 + -9 + 1x = 5 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 5 + -9 1x = 5 + -9 Combine like terms: 5 + -9 = -4 1x = -4 Divide each side by '1'. x = -4 Simplifying x = -4
| 3x-1/x-4 | | 460=24n+4 | | 6y-2(y+1)=(y-2)+6 | | 7x+11=3(x+y) | | (3d)(3d)(d-7)=0 | | X+(X*0.75)=608 | | 5(x-4)-(12-x)=11+6(1+x) | | 28b-21/7 | | 78=15+21b | | (4z-1)(3-z)=0 | | f(x)=x^6+7x^3-8 | | (11b-3)-5(2b+2)=-3 | | X/7=7/6 | | -130=5(6m+5)+m | | 4x+59-63=12 | | 13=a+2 | | -5(3b+1)+(16b-1)=0 | | -155=31m | | 2x+4*2=2*(x+2) | | Z/5=4/3 | | 4x+6=7x+3(2-x) | | [10-20]-[-7]= | | 130=31m+25 | | 5.12-3.34x=2x-1.555 | | Log[3](-7-4x)=1 | | 5x+8x+11=180 | | 3.17x+1.11=2.8x | | 364=8b-5(8b+4) | | 5(a+2)(a-4)=0 | | -32-49-3x=-12x | | 9z^2-54z+76= | | 96=8(6-a) |